(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In the publication multi factor authentication solutions are offered as a necessary tool for decrease of information technology security risks. The work includes description of authentication process from the viewpoint of information technology security aspect, as well as authentication factors are described, which can be used in authentication process modules. Some recommendations for decrease of security risks are given using multi factor authentication solutions. In the work a multi-factor authentication security testing experiment is described, which involves use of Linux remote console - SSH service. Analysis of data of unauthorised access efforts obtained during tests is described: it is determined from which countries or regions, as well as in which days there is the highest threat to information technology security.